2022
DOI: 10.1590/1806-9061-2021-1502
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Phytase with Or without Organic Acid (Sodium Di-Formate) Supplementation on Growth Performance, Carcass Response, Protein and Mineral Digestibility in Starter Phase of Broilers

Abstract: This experiment was planned to evaluate the effects of phytase supplementation with or without organic acid (OA) on performance, protein, calcium (Ca), phosphorus (P) and sodium (Na) digestibility and carcass parameters in broiler chickens fed low Ca and low P diets in comparison to a high Ca and high P diet with standard specifications. For this purpose, two iso-nitrogenous and iso-caloric diets were prepared in such a way that one diet had high Ca (9.80) and high P (4.50) and second diet had low Ca (8.50) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…During days 52 to 54, the broilers were fed an experimental diet and complete excreta were collected for 3 days ( 21 ). Excreta were collected thrice per day (07:00, 12:00, and 19:00 h) from each fecal tray under cages, weighed the weight of chicken excreta, mixed evenly, collected about 100 g of chicken excreta samples, and stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…During days 52 to 54, the broilers were fed an experimental diet and complete excreta were collected for 3 days ( 21 ). Excreta were collected thrice per day (07:00, 12:00, and 19:00 h) from each fecal tray under cages, weighed the weight of chicken excreta, mixed evenly, collected about 100 g of chicken excreta samples, and stored at −20°C.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that organic acid decreases the pH of the broilers, and adding it to diets increases the effectiveness of added phytase [ 4 , 5 ]. Additionally, the synergistic effect of dietary phytase with citric acid (CA) was informed by several scientists [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering these circumstances, it may be applicable to conduct research on broilers fed inorganic P free diets, but phytase. Several studies have been conducted using phytase in broilers diet, but in most cases, diets contained inorganic P (Ebrahimnezhad et al, 2008;Nezhad et al, 2011;Nourmohammadi et al, 2010Nourmohammadi et al, , 2012Mohammadagheri et al, 2016;Demirel et al, 2021;Anwar et al, 2022). Besides, organic acid such as citric acid (CA) is a well-recognized feed additive that is recently used in broiler diets to increase nutrient digestibility, mineral retention (Chowdhury et al, 2009;Islam et al, 2012) as well as enhance phytase activity (Vieira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%